All-biomaterial supercapacitor derived from bacterial cellulose. Issue 17 (19th April 2016) - Wang, Xiangjun; Kong, Debin; Zhang, Yunbo; Wang, Bin; Li, Xianglong; Qiu, Tengfei; Song, Qi; Ning, Jing; Song, Yan; Zhi, Linjie
Abstract : To fabricate the all bio-material supercapacitor, both the electrode (APBC) and the gel electrolyte (BC–H3 PO4 were obtained from BC through different methods, which displays an improved specific capacitance of 289 mF cm −2 and higher capacitance retention compared with the PVA-electrolyte supercapacitor.) Abstract : An all-biomaterial originated film supercapacitor has been successfully fabricated for the first time based on a unique three-dimensional bacterial cellulose (BC) derived electrode and a novel BC-based gel electrolyte. The obtained supercapacitor displays an excellent specific capacitance of 289 mF cm −2 and an improved solution resistance of 7 Ω.